Student Perceptions of the Ophthalmology Curriculum in Medical School - Cobbs, Lucy; Tsui, Edmund; Haberman, Ilyse D.; Kim, Eleanore; Sperber, Laurence; Wu, Mengfei; Schuman, Joel S. (Journal of Academic Ophthalmology, 2018)
Purpose There is no national standard for ophthalmology curricula in U.S. and Canadian medical schools. We aim to evaluate medical students' perceptions of the current ophthalmology curriculum without mandatory rotation at New York University School of Medicine (NYUSOM).Design A cross-sectional Internet survey.Methods A cross-sectional Internet survey was distributed to all NYUSOM students in March to May 2017. The main parameters measured in the study were students' self-reported confidence with ophthalmology skills and satisfaction with curriculum.Results Response rate was 27.5% (166 of 604) of NYUSOM students. Many students reported they were not comfortable diagnosing eye emergencies (64%), using a direct ophthalmoscope (71%), or testing visual acuity (50%). The majority of students did not want ophthalmology to become a mandatory rotation, but reported additional in-person training would be most helpful, compared with videos, web-based didactics, lectures, or virtual training. Completion of an ophthalmology elective and more hours of ophthalmology training were associated with increased confidence with eye examination and greater satisfaction with the curriculum.Conclusions It is critical for all physicians-in-training to have adequate skills in eye examination. Identifying areas of improvement and determining the best teaching modality will be important in updating the ophthalmology curriculum for medical students. The majority of medical students are not at all or only slightly confident with eye examinations. Increasing the amount of in-person ophthalmology training in medical school improves confidence with eye examination.
Keywords: medical school; education; ophthalmology; curriculum